Hypoglycemic coma during treatment with propranolol. - Milano, A. (European Journal of Pediatric Dermatology, 2020)
We described (1) another case of hypoglycemia, also in that case many months after the start of therapy with propranolol. For this reason, although in the Hemangiol® leaflet it is not recommended to periodically check blood sugar, we have continued to have it performed by the mother periodically, also to sensitize her to the problem. However, despite this habit and the repeated advice to the mother to reduce or stop the drug when the child does not eat, we observed 2 cases of propranolol-induced hypoglycemia in 400 children treated with the drug. In the literature there is no shortage of such cases. This side effect is not probably related with the dose of the drug (2), but it is often associated with fasting, as occurred in our cases. Therefore, it is necessary to further sensitize dermatologists, pediatricians and parents to this rare but severe side effect of propranolol therapy.